Fundamentals of metal-matrix composites - Suresh, S. (Subra); Mortensen, A. (Andreas); Needleman, A. (Butterworth-Heinemann, 1993)
Focuses on the following areas of metal composites: processing, microstructure and characterization, mechanics and micromechanics of deformation, mechanics and micromechanics of damage and fracture, and practical applications.